2018 IEEE Symposium on Security and Privacy (SP) 2018
DOI: 10.1109/sp.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

Speechless: Analyzing the Threat to Speech Privacy from Smartphone Motion Sensors

Abstract: According to recent research, motion sensors available on current smartphone platforms may be sensitive to speech signals. From a security and privacy perspective, this raises a serious concern regarding sensitive speech reconstruction, and speaker or gender identification by a malicious application having unrestricted access to motion sensor readings, without using the microphone.In this paper, we revisit this important line of research and closely inspect the effect of speech on smartphone motion sensors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…There are opposing views on whether non-acoustic smartphone sensors capture sounds at normal conversational loudness. While Anand and Saxena did not notice an apparent effect of live human speech on motion sensors in several test devices [3], other studies report very small but measurable effects of machine-rendered speech, significant enough to reconstruct spoken words or phrases [54,79].…”
Section: Experimental Research Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are opposing views on whether non-acoustic smartphone sensors capture sounds at normal conversational loudness. While Anand and Saxena did not notice an apparent effect of live human speech on motion sensors in several test devices [3], other studies report very small but measurable effects of machine-rendered speech, significant enough to reconstruct spoken words or phrases [54,79].…”
Section: Experimental Research Findingsmentioning
confidence: 99%
“…Initially, speech is recorded through the smartphone by an actor B, which could be either (1) the operating system provider itself, e.g. Apple or Google, (2) non-system apps installed on the device, or (3) third-party libraries 3 included in these apps. Potentially after some processing and filtering, which can happen locally on the device or on remote servers, actor B shares relevant information extracted from the recordingdirectly or through intermediarieswith organization A (unless A and B are one and the same actor, which is also possible).…”
Section: Threat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Michalevsky et al showed that MEMS gyroscope measurements are sensitive to acoustic signals in their vicinity [174]. As a result, they can be used to distinguish between different speakers, and, in part, the content of the speech [174] due to conducted vibrations of the loudspeakers used [175], [176].…”
Section: Additional Related Workmentioning
confidence: 99%
“…In other words, the same source of vulnerability which can be used to destabilize [10] and control [13], [34], [43] gyroscopes and accelerometers can be used for covert channel communication [171], [172], tracking [173], and speaker identification [174], [175]. Similarly, instead of using microphone non-linearities for command injections [11], [55], [134], Shen et al [177] and Chen et al [178] leveraged them to protect users' privacy by jamming nearby recording devices.…”
Section: Additional Related Workmentioning
confidence: 99%